New Galumnoidea (Acari, Oribatida) from Tanzania - Ermilov, Sergey G.; Khaustov, Alexander A. (Zootaxa, 2019)
Three new species of oribatid mites of the superfamily Galumnoidea are described from litter in the mixed forest of Zanzibar, Tanzania: Pergalumna hugocoetzeeae sp. nov., Pergalumna pietertheroni sp. nov. (both Galumnidae) and Galumnella paraokinawana sp. nov. (Galumnellidae). An identification key to the known species of the genus Galumnella from the Ethiopian region is presented.